Ecuador : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
The country brief provides and overview of Tobacco Use, Tobacco Control Legislation, and Taxation in Ecuador. Ecuador has a strong tobacco control policy. A comprehensive tobacco control law was adopted and implemented. In 2017, Ecuador was awarded the World No Tobacco Day Prize of the World Health Organization (WHO) for its tobacco control efforts and implementation of the WHO Framework Convention on Tobacco Control (FCTC). Such policy was very beneficial to public health: according to the National Institute of Statistics and Censuses (INEC), the prevalence of daily smoking among people aged 15 years and older was 9.5 percent in 1998, and in 2014 it reached 2.8 percent. Estimated annual cigarette consumption in Ecuador declined from about three billion cigarettes in 2007-2010 to about one billion cigarettes in 2017. The pricing policy of the tobacco industry also contributed to the reduction in cigarette affordability and cigarette sales in Ecuador. However, due to such pricing policy, the tobacco industry apparently increased its profits despite the sharp decline in cigarette sales in the country. These recommendations could bring both public health and fiscal benefits to Ecuador : specific excise rate for cigarettes should be annually increased by at least 20 percent to ensure the reduction in tobacco affordability and the increase in the excise revenues, tobacco use surveillance and monitoring should be further developed in Ecuador, including a regular collection of information on smoking prevalence, tobacco consumption, licit and illicit cigarette sales, prices, and other economic indicators, and effective policies to counteract tobacco smuggling and other kinds of illicit tobacco sales should be implemented in line with the provisions of the FCTC Protocol to Eliminate Illicit Trade in Tobacco Products.